2013
DOI: 10.1371/journal.pone.0056564
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Signatures of Extreme Longevity in Northern Italian Centenarians Reveal a Complex Remodeling of Lipids, Amino Acids, and Gut Microbiota Metabolism

Abstract: The aging phenotype in humans has been thoroughly studied but a detailed metabolic profiling capable of shading light on the underpinning biological processes of longevity is still missing. Here using a combined metabonomics approach compromising holistic 1H-NMR profiling and targeted MS approaches, we report for the first time the metabolic phenotype of longevity in a well characterized human aging cohort compromising mostly female centenarians, elderly, and young individuals. With increasing age, targeted MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
180
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(199 citation statements)
references
References 59 publications
14
180
3
2
Order By: Relevance
“…Linoleate is the most abundant fatty acid in atherosclerotic plaques, and high levels of HODEs accumulate in the low-density lipoprotein (LDL) and plaque of patients with atherosclerosis compared with healthy controls (14). Similar to F 2 -IsoP, the HODEs are stable lipid peroxidation products that are elevated in diseased individuals and can be lowered through positive lifestyle changes (2,3,7,25,29,37). The data from this study support the use of 13-HODE ϩ 9-HODE as biomarkers of oxidative stress during exercise trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linoleate is the most abundant fatty acid in atherosclerotic plaques, and high levels of HODEs accumulate in the low-density lipoprotein (LDL) and plaque of patients with atherosclerosis compared with healthy controls (14). Similar to F 2 -IsoP, the HODEs are stable lipid peroxidation products that are elevated in diseased individuals and can be lowered through positive lifestyle changes (2,3,7,25,29,37). The data from this study support the use of 13-HODE ϩ 9-HODE as biomarkers of oxidative stress during exercise trials.…”
Section: Discussionmentioning
confidence: 99%
“…13-HODE ϩ 9-HODE are stable oxidation products and have been linked to pathological conditions including atherosclerosis, diabetes, Alzheimer's disease, non-alcoholic steatohepatitis, psoriasis, chronic inflammation, obesity, and cancer (14,23,29,37). Plasma levels of 13-HODE ϩ 9-HODE are responsive to lifestyle interventions, with decreases reported when subjects adopt healthy diets and lose excess body weight (2,3,7,25). 13-HODE ϩ 9-HODE are generated through the 15-lipoxygenase-1 (15-LOX) pathway in a variety of cell types (17,25), are ligands of peroxisome proliferator-activated receptors (PPARs) (28), and can act through G protein-coupled receptor 132 (GPR132) to exert pro-inflammatory effects (37).…”
mentioning
confidence: 99%
“…Indeed, metabolomics has been recently used for the identification of novel biomarkers and the elucidation of novel biological pathways for a variety of diseases (15,17). For example, Collino and co-workers studied the metabolic phenotype of longevity by comparing the metabolomics profile of centenarians, elderly, and young people (18,19). In this study, alterations of the glycerophoshpolipids and sphingolipids were observed in the centenarian population, helping elucidate mechanistic routes for the longevity phenotype and demonstrating the power of this method.…”
mentioning
confidence: 86%
“…The results concerning centenarians are somehow conflicting, describing, depending on the systems studied, a vigorous youth-like response different from 'usual' elderly or, if not different, it is compensated by various other phenomena which decrease the occurrence of inflammation-dependent chronic diseases [36,37]. In line with the described metabolic changes strongly impacting on longevity through evolution, a recent study in subjects with extreme longevity in Northern Italy found that complex remodeling of lipid, amino acid metabolism and of gut microbiota functionality are key regulatory processes marking exceptional longevity in humans via the modulation of the oxidative and inflammatory processes [38]. Moreover, recent studies also suggest that the differences in supercentenarians are the 'compression of morbidity' signifying that cardiovascular diseases or cancer appear very late in these subjects because of the increased genetic background, conferring a very beneficial variant which protects these individuals from lifelong aggressions [39,40].…”
Section: Did Studies On Centenarians Help Us To Better Understand Agimentioning
confidence: 90%